Laparoscopic compatible device incorporating inductive proximity sensors for precise detection of gastric and colorectal small tumors - Calborean, Adrian; Macavei, Sergiu; Mocan, Mihaela; Ciuce, Cătalin; Cordos, Adrian; Bintintan, Adriana; Chira, Romeo; Pestean, Cosmin; Pop, Oana; Barbu-Tudoran, Lucian; Dindelegan, George; Surlin, Valeriu; et al. (Surgical oncology, 2020)
The accurate localization of small tumors of the digestive tract is of paramount importance in surgical oncology because it dictates the limits of resection and the extent of lymph node dissection. In this view, we have designed and fabricated a highly efficient sensing laparoscopic instrument focused on precise non-invasive extralumenal intraoperative detection of small colorectal or gastric tumors. The equipment is fully adapted for laparoscopic surgery and consists of an inductive proximity sensor encapsulated into a watertight stainless-steel case that is connected to an electronic functional block dimensionally scaled-down by the desired form and size for optimal surgical manipulation. The sensor-case unit and the electronic block are coupled together using a modular system which allows disconnection of the latter and sterilization by autoclavation of the former, followed by swift plugging of the electronic block just before surgery in a sterile-controlled environment. The instrument works in tandem with a modified endoscopic hemostatic clip which is attached endoscopically, before surgery, in the mucosa proximal and distal to the tumor. By scanning the serosal side of the digestive organ during the laparoscopic surgical procedure, the detector senses the modified clip and thus pinpoints to the location of the tumor. Additional engineering of the standard endoscopic hemostatic clips by coating them with various combinations of metallic alloys of Cu and Zn was necessary to improve the detection range and sensitivity without compromising on their functionality. The clips were also covered with nanometric layers of Au to ensure their biocompatibility. The ex-vivo dry-lab experiments showed a satisfactory detection distance which was later confirmed in ex-vivo wet-lab experiments on animal organs and human surgical specimens.
Gesehen am 07.02.2022